2002
DOI: 10.1094/mpmi.2002.15.3.243
|View full text |Cite
|
Sign up to set email alerts
|

A Tobacco S-like RNase Inhibits Hyphal Elongation of Plant Pathogens

Abstract: Ribonuclease (RNase) NE gene expression is induced in tobacco leaves in response to Phytophthora parasitica. Using antibodies directed against RNase NE, we demonstrate that RNase NE is extracellular at the early steps of the interaction, while the fungal tip growth is initiated in the apoplastic compartment. After production in Pichia pastoris and biochemical purification, we show that the S-like RNase NE inhibits hyphal growth from P. parasitica zoospores and from Fusarium oxysporum conidia in vitro. Conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…Such genes likely originate as paralogous copies of S-alleles. Many more-distantly related genes in the same RNase superfamily exist, but with much lower amino-acid identities, and they are expressed in other plant tissues (for example, Hugot et al, 2002). We found that the putative S-alleles we sequenced co-segregated with S-allele phenotypes by performing a series of half-compatible crosses to test the association between sequence and functional phenotype.…”
Section: B Igic Et Almentioning
confidence: 93%
“…Such genes likely originate as paralogous copies of S-alleles. Many more-distantly related genes in the same RNase superfamily exist, but with much lower amino-acid identities, and they are expressed in other plant tissues (for example, Hugot et al, 2002). We found that the putative S-alleles we sequenced co-segregated with S-allele phenotypes by performing a series of half-compatible crosses to test the association between sequence and functional phenotype.…”
Section: B Igic Et Almentioning
confidence: 93%
“…The function and mode of action of the non-S-RNase PA1 is still unknown, although there are clearly some similarities with the S-RNases, in that they are pistil-specific basic RNases (Yamane et al, 2003). It is known that some acidic non-S-RNases are induced by wounding and pathogen infection (Ye and Droste, 1996;Galiana et al, 1997;Kariu et al, 1998;Hugot et al, 2002;LeBrasseur et al, 2002); however, PA1 mRNA levels are neither induced by wounding nor by salicylic acid application (data not shown). Since PA1 is a pistil-specific protein, the suggestion is that its function is more likely to be related to reproduction, as with S-RNases (Murfett et al, 1996;Hancock et al, 2003), rather than part of a wounding or disease response.…”
Section: Discussionmentioning
confidence: 97%
“…Tobacco RNase NE expression is induced in response to Phytophthora parasitica, and purified RNase NE can inhibit hyphal elongation of this pathogen (Hugot et al 2002). Other Nicotiana genes, RNase NW, and RNase Rk1, are induced in response to tobacco mosaic virus and cucumber mosaic virus infections, respectively (Kurata et al 2002;Ohno and Ehara 2005).…”
Section: Introductionmentioning
confidence: 99%